Il corpo sonoro del Living Theatre per "Antigone": (su nastro magnetico Rai, 1967) - Marinai, Eva (Mimesis Journal, 2014)
Italy’s national public radio broadcasting company (Radio Rai) has just celebrated its ninetieth year of transmissions. A document found in the Radio Tape Archive gives a unique testimony to the work of the Living Theatre for Antigone, in its first version in 1967. Gerardo Guerrieri, in fact, transcribes a script of the radio show, starting with the editing of live audio recordings made during the performances at Theatre of the Arts in Rome, in the spring of 1967, and interlacing it with voices describing the actions performed, as well as Malina’s Director’s Notes. Thus it provides a critical interpretation of the rites acted by the company. This «sound version» of the show, titled The protest of Antigone, broadcasted on July 8, 1968 in the “Third Programme” (later known as Radio 3), allows to focus on the rhythmic score and on the tuning of the Living Theatre “Body/Choir”. What emerges is an “absolute sound mise-en-scène” (Malina), which confirms, once again, the ability of these actors to create a polysemic work of art, able to communicate at all levels of perception, not only visual but also – and in a no less incisive way – psychoacoustic.